THE INFLUENCE OF ORGANIZATIONAL CITIZENSHIP BEHAVIOR AND TALENT MANAGEMENT ON PRODUCTIVITY WITH INNOVATION AS A MEDIATING VARIABLE (CASE STUDY PT NESINAK INDUSTRIES CIKARANG) - Niken Mayang Sari; Muhamad Ekhsan (Sekolah Tinggi Ilmu Ekonomi Sultan Agung, 2024)
. This study aims to analyze the effect of Organizational Citizenship Behavior (OCB) and Talent Management on productivity, with Innovation as a mediating variable at PT Nesinak Industries, Cikarang. This quantitative research involves a population of employees in the PT Nesinak Industries area, by collecting data using a questionnaire distributed through an application called Google Form. Data analysis was carried out using the Smart PLS method. The results showed several findings that supported the hypotheses. First, OCB does not contribute significantly to productivity, which is influenced by the lack of recognition and reward for organizational citizenship behavior. Second, Talent Management also did not make a significant contribution to productivity, constrained by the lack of clarity in job appraisal. Third, OCB has no significant effect on innovation due to the lack of clear support for innovation. Fourth, Talent Management is able to make a significant contribution to innovation, but is still hampered by the lack of flexibility in the organization. urthermore, innovation did not make a significant contribution to productivity, influenced by the lack of support from leaders. Furthermore, OCB is unable to make a significant contribution to productivity through innovation due to the lack of leader involvement. Finally, Talent Management was also unable to make a significant contribution to productivity through innovation, affected by the lack of recognition and rewards in an innovative context. This research provides an in-depth understanding of the dynamic relationship between OCB, Talent Management, innovation, and productivity in a manufacturing organization environment. Managerial implications and practical recommendations are also discussed, creating a foundation for continuous improvement at PT Nesinak Industries.